2022
DOI: 10.3390/molecules27196326
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Tail and Head-to-Head Molecular Chains of Poly(p-Anisidine): Combined Experimental and Theoretical Evaluation

Abstract: Poly(p-anisidine) (PPA) is a polyaniline derivative presenting a methoxy (–OCH3) group at the para position of the phenyl ring. Considering the important role of conjugated polymers in novel technological applications, a systematic, combined experimental and theoretical investigation was performed to obtain more insight into the crystallization process of PPA. Conventional oxidative polymerization of p-anisidine monomer was based on a central composite rotational design (CCRD). The effects of the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…In polymeric materials, similar functional moieties in different stereochemical and compositional environments experience distinctive chemical environments, thereby inducing variations in the chemical shis of various 1 H nuclei. 34 As a result, the spectrum of a polymer can exhibit overlapping neighboring signals with a similar spectral prole, as observed in the 1 H NMR spectrum of PPA in Fig. 2.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…In polymeric materials, similar functional moieties in different stereochemical and compositional environments experience distinctive chemical environments, thereby inducing variations in the chemical shis of various 1 H nuclei. 34 As a result, the spectrum of a polymer can exhibit overlapping neighboring signals with a similar spectral prole, as observed in the 1 H NMR spectrum of PPA in Fig. 2.…”
Section: Resultsmentioning
confidence: 54%
“…Rodrigues de Oliveira et al observed that the ratio of monomer to oxidant had a signicant effect on polymer structure and pellet conductivity. 34 ATR-FTIR spectroscopy was used to compare the IR peaks of the p-anisidine (PA) monomer vs. the PPA polymer, and to further validate a successful polymerization. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations